2013
DOI: 10.1177/1545968313484810
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Single-Session Repetitive Transcranial Magnetic Stimulation Applied Over the Hand Versus Leg Motor Area on Pain After Spinal Cord Injury

Abstract: rTMS applied over the hand or leg motor cortex decreased neuropathic pain regardless of any change in cortical excitability, suggesting that the analgesic effect is not associated with local changes at the motor cortex level itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 30 publications
2
71
0
Order By: Relevance
“…Three RCTs in SCI-related NP compared the effect of transcranial magnetic stimulation with sham therapy. [54][55][56] Two of these trials found no significant difference in reduction in pain intensity. 54,55 The evidence quality of the third trial, which found a significant improvement in pain intensity after treatment, was downgraded because of wide confidence intervals.…”
Section: ) Treatments With Low-quality Evidence Of Positive Effectmentioning
confidence: 98%
See 1 more Smart Citation
“…Three RCTs in SCI-related NP compared the effect of transcranial magnetic stimulation with sham therapy. [54][55][56] Two of these trials found no significant difference in reduction in pain intensity. 54,55 The evidence quality of the third trial, which found a significant improvement in pain intensity after treatment, was downgraded because of wide confidence intervals.…”
Section: ) Treatments With Low-quality Evidence Of Positive Effectmentioning
confidence: 98%
“…54,55 The evidence quality of the third trial, which found a significant improvement in pain intensity after treatment, was downgraded because of wide confidence intervals. 56 2) Treatments with evidence of positive effect in populations other than SCI The SC evaluated several therapies with evidence of pain reduction in non-SCI populations, including cannabinoids, duloxetine and intrathecal clonidine.…”
Section: ) Treatments With Low-quality Evidence Of Positive Effectmentioning
confidence: 99%
“…2 To date, most studies have targeted the primary motor cortex (M1), mainly contralateral to the pain side, 3 whereas fewer studies reported analgesic effects after stimulation of other cortical areas, such as the prefrontal cortex (PFC)/dorsolateral PFC (DLPFC). [4][5][6][7][8] Also for managing neuropathic pain in subjects with spinal cord injury (SCI), M1 has been a popular target, [9][10][11][12][13][14] but it is unclear whether M1 is the only effective cortical target. To date, no studies have thoroughly investigated the effects of stimulation of other cortical targets (that is, PFC, parietal areas, supplementary motor area, primary or secondary somatosensory cortex) on neuropathic pain in SCI patients.…”
mentioning
confidence: 99%
“…Ylmaz et al 34 have shown significant pain decrease in these patients, however statistical analysis used in this study has not compared interaction between group and time. Both hand and lower limb stimulation seem to have better effect as compared to simulated stimulation 35 , however this was not shown in an initial study 36 . An important factor might be the number of administered pulses, since studies with around 500 to 1000 pulses by session have not shown analgesic effect 36,37 .…”
Section: Physical Rehabilitation For Neuropathic Pain After Central Nmentioning
confidence: 84%